(untitled) (Global Journal of Human-Social Science, 2015)
Increasing need for accountability, combined with competition for educational resources, necessitates movement toward a culture of scholarship at institutes of higher education. Transitioning toward such a culture, particularly for smaller institutions or those focused primarily on teaching, can be challenging due to changing expectations on issues such as workload and productivity. As part of a broader effort to build infrastructure at a single academic institution, we describe a case study to inform a process of cultural change to promote scholarship. We reviewed existing literature on scholarship and productivity, and we interviewed 30 faculty and doctoral students at a transitioning college of social work regarding their scholarship. Analyses were conducted using provisional, axial, and selective coding and MaxQDA software. We identified five key themes for promoting a culture of scholarship, including protecting time for research, building staff supports, engaging students, developing research resources, and cultivating professional growth and discourse. Specific recommendations in the five areas and a checklist of strategies can be used to implement change at other institutions. The suggested strategies are derived from faculty and student perspectives, thereby allowing those held to expectations to take a lead role in building infrastructure within an evolving academic context.